A Preliminary Study on Heavy Oil Location in Central Sumatra using Remote Sensing and Geographic Information Sytem - Suliantara Suliantara; Tri Muji Susantoro; Herru Lastiadi Setiawan; Nurus Firdaus (Testing Center for Oil and Gas LEMIGAS, 2021)
Heavy oil which is classifi ed as non conventional oil is the target of exploration in the world. In Indonesia, the potential for heavy oil exploration is quite large, especially in the Central Sumatra basin. This study aims to map the location of potential heavy oil based on remote sensing data and regional gravity data supported by a geographic information system. Landsat 8 OLI satellite data is processed to produce 567 (RGB) color composite images, then further processing is carried out with DEM data to produce fusion images; mapping the vegetation index, clay mineral index, iron oxide index, surface temperature. The gravity data is used for mapping subsurface geological structures. Overlay analysis is carried out on the results of remote sensing data processing and interpretation of surface and subsurface geology. Based on the analysis, it shows that heavy oil fi elds are generally found on the surface and subsurface structures which are relatively identical and located on the edge of the basement high. Based on this analysis, the locations that have the potential for heavy oil and gas traps are on the northeast edge, Dalu-dalu High, the edge of Kampar High, the west edge of Kuantan High, the southwest edge of the Beruk High, the southwest edge of the Sembilan High.